Towards playing AIs for 7 Wonders: main patterns and strategies for 3-player games - Bettker, Rafael; Minini, Pedro; Pereira, Gabriel; Assunção, Joaquim V. C. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Artificial Intelligence (AI) in games may be greatly supported by a robust set of patterns, rules, and strategies that contribute to securing a win. In this work, we made a Knowledge Discovery pipeline – involving data selection, association, classification, and clustering – to successfully identify important factors that help to achieve a win in the board game 7 Wonders, focusing on 3-player matches. Our results show strong patterns and main strategies used by the best players in the world. This knowledge narrows the search for a Nash equilibrium for the game, getting us closer to create a top-tier AI.